TRADISI BULAN RAMADHAN DAN KEARIFAN BUDAYA KOMUNITAS JAWA DI DESA TANAH DATAR KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Yuhana "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The Javanese culture is one of the important cultural culture among other areas in thelife of nation and State in the past and currently. In the culture and life of Java containedvalues into guidelines and handle living community. The Islamic community incommemorating the holy month of Ramadan, often doing something custom to welcome themonth. The villagers of this flat land in the habit of welcoming (before), do (fast), even afterthe holy month of Ramadan (IdulFitri). As for the tradition of fasting before sending such as:Punggahan, selikuran, Pudunan, Riyoyo and Kupatan. Villagers flat land in following suchevents always bring food to places of worship for me to perform a ritual event that tradition.The food that they carry this symbol for Javanese who carry out. This research wasconducted with Qualitative Descriptive method and sampling in Purposive Sampling. Thesample consists of the head of the village of Tanah Datar, religious figures, Figures, figuresof indigenous youth, female character, Scholarship, and four representatives from thecommunities that follow the tradition on the month of Ramadan. In this study, the authors tryto tell and explain how the process of Ramadan traditions made by the Java community in thevillage of flat land. The results of the interviews and observations of researchers for thesamples taken, researchers figure out how to process the ritual tradition of Javanese peopleresiding in the village.Furthermore, the researchers also revealed the existence of valuescelebrating the wisdom contained in the Ramadan local traditions On JavaCommunity in thevillage.Key words: tradition, Cultural Discernment, community